Coleção Girassol : livro didático de alfabetização em contexto indígena - (des)encontros entre o proposto e o realizado - Silva, Marta Cecília Rocha da (2015)
This study aims to analyze the Textbook Literacy (LDA), the intercultural perspective in the process of teaching and learning in a context where Portuguese is the second language. For this work will be performed with teachers of the first stage of primary school into the three units School in Indigenous Bakairi at the municipality of Paranatinga, Mato Grosso. The overall objective is to analyze the first three volumes Collection Sunflower - Knowledge and Doings Field. Distributed and approved by PNLD Field in 2013 and its adaptation to the context of multi-cultural and linguistic diversity as indigenous schools in the literacy process between Bakairi ethnicity. The aim is to point adequacy or inadequacy of the LDA, in relation to the objectives for which it was prepared and its implications in the context of school of Indian countryside and the National Curriculum Guidelines for Indigenous Education (DCNEI) for this scenario, contextualize the environment where the LDA is used, in terms of cultural and linguistic diversity. The aim is also to analyze the observed aspects generating contribution based on notes from teachers about the problem. The methodology for data collection is to examine, in the context of intercultural education, the teaching of literacy book (LDA), distributed by PNLD Field, the DCNEI and in addition, the use of interviews with four teachers. The data analysis identified that the interviewed teachers use the LDA as collateral in everyday school life and enable students and themselves as subjects of pedagogical practice, a close experience with the form that enables greater ownership of texts presents. The challenge of interculturalism is present in encouraging cultural production, LDA share on school and family experiences. We also noticed that the experiences of the early years of schooling by the teachers allow them to participate in the "construction" of knowledge to their students today. The volumes analyzed, at first, it is observed that, even though it was presented as approved for the education field, the aspects of an intercultural education could have the spotlight. You can see a fairly succinct attitude to linguistic diversity and indigenous issues, one of the groups that make up the rural areas population. Note also that important teaching support resource has multiple functions in bilingual literacy process.